Effect of GeCl4/SiCl4 flow ratio on germanium incorporation in MCVD process - Mat Sharif, Khairul Anuar; Zulkifli, Mohd Imran; Muhamad Yassin, Shahrin Zen; Tamchek, Nizam; Aljamimi, Salah Mohammed; Yusoff, A.; Mohd Amin, Yusoff; S. A., Siti Shafiqah; Abdul Rashid, Hairul Azhar (IEEE, 2013)
Germanium and Silica co-deposition in MCVD process is studied with varying the flow ratio of GeCl4/SiCl4 at high temperature without phosphorus. The range of ratio is from 0.1 to 0.6 with temperature deposition 2100°C. The incorporation of germanium in silica matrix is deduced from the EPMA SEM-EDX. The experimental result is compared to theory such as thickness deposited layer and mole fraction of germanium in silica.